Effects of natural products on skin inflammation caused by abnormal hormones secreted by the adrenal gland - Xie, Wei; Zhang, Ce; Wang, Tian; Wang, Jianshe; Fu, Fenghua (Frontiers in Pharmacology, 2023)
The cortex of adrenal gland produces glucocorticoid, mineralocorticoid, and androgen. The medulla of adrenal gland secrets catecholamines. These hormones play an important role in regulating blood pressure, metabolism, and homeostasis of glucose or electrolytes. Hypersecretion or hyposecretion by the adrenal gland will cause a complex cascade of hormone effects and lead to diseases, including Addison's disease, Cushing's syndrome, and congenital adrenal cortical hyperplasia. Skin is the largest organ of body. It provides protection and acts as a barrier against external damage factors like infectious organisms, chemicals, and allergens. Endocrinologic disorders often induce cutaneous abnormalities. According to the previous evidences, natural products have the potential properties for attenuating skin disorders and improving dermatologic symptoms by inhibiting inflammation through MAPK or PI3K/AKT-dependent NF-κB pathways. The natural products may also promote skin wound healing by inhibiting the production of matrix metalloproteinase-9. We systematically searched the relevant articles from databases, including PubMed, Embase, and Cochrane library databases, to review the effects of natural products on skin disorders. This article summarized the effects of natural products on skin inflammation caused by the abnormal secretion of hormone of adrenal gland. And the published papers indicated that natural products might be a potential source for treating skin diseases.